Optimum design of sofc based polygeneration system for residential area with vehicle charging or fueling station / Farah Ramadhani - Farah , Ramadhani (2019)
The residential sector is one of the energy consumers in the world generally, and in Malaysia, especially. Integrated energy supply which can simultaneously generate multienergy types for fulfilling the demand of residential and vehicle users called polygeneration system is promising as the future and modern energy supply design. This study proposes a modern energy supply design for the residential area with considering stationary power and vehicle applications. The proposed system can generate electricity, hot water, and cooling system for the building. The system also provides power and hydrogen supplied to vehicle charging or fueling station in the private area. The polygeneration employs solid oxide fuel cell as a prime mover for heat and power generation. This study optimizes the design of polygeneration through four steps to overcome the deficiency in the system, increasing energy savings, cost savings and minimizing carbon emission generated from the system. The first step, four configurations of the proposed design based on grid connection and type of vehicle to be served was evaluated. Next, the reliability of polygeneration system was improved by adding renewable energy, a thermoelectric device, and energy storage to increase the efficiency of the system. The third step was to design the optimum operating strategy to increase the reliability and primary energy saving reduce the energy cost and carbon emission. The last step was to develop the optimum size for the system component by using evolutionary and swarm based optimization algorithm. The results in the first step revealed the advantages of the SOFC based polygeneration system over the conventional separated system with several improvements in energy saving, energy cost savings and carbon emission of about 36%, 50% and 33%, respectively. Amongst four configurations studied in the first step, the standalone polygeneration with electric vehicle becomes the optimum configuration chosen as it has high energy saving, energy cost saving, and a good emission reduction. This study also proved the effect of the hydrogen selling strategy in decreasing the energy cost of the polygeneration system by about 51% and improves the system to be more economically competitive against the conventional separated system. The results of the second step of this study confirmed that the polygeneration with added extra heat recovery system achieves the gains of reliability, efficiency, and energy saving by about 35.91%, 14.36%, and 11. 58%, respectively. The optimum operating strategy based on Fuzzy operation gives significant improvements on the efficiency, energy saving, and cost saving by about 4%, 112%, and 33% respectively compared to the conventional polygeneration. The optimal polygeneration capacity using genetic algorithm achieves improvements in primary energy saving, cost saving and carbon reduction by up to 65.1%, 42.4% and 62.6% respectively. It also confirms the stability of the optimizing process by running the optimization cycles in several times and attaining the deviation by about 2%.